Implementation of Student Worksheets with Android-Based on Natural Science Subject - Deni Setiawan; Erika Wahyu Nurani; Arif Hidayat (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This study was conducted cause the student's learning outcomes were less successful. Based on the Midterm Assessment (PTS) evaluation at SDN 2 Mojo, 27 students (25%) were incomplete. Based on the data, the lowest value is 40, and the highest value is 80. The research adopts the ADDIE model with Mollena and Januszewski's theories: analyze, design, development, implementation, and evaluation. Research gets the following results: 1) Student Worksheet with the android system for Natural Science learning activities with style material created using the Android Studio application, operating through the lollipop type android system; 2) Student Worksheets with developed android systems included in the criteria were very feasible; Assessment was carried out by material and media experts with an assessment of the presentation component 90%, while the feasibility of content with a value of 92%; 3) The student worksheet was effective as a learning facility in Natural Science learning. The average pre-test value was 55.57143, and the post-test with a value of 80.88571. The t-test results showed that tcount ≤ - ttable with tcount calculation of -14,463 less than the ttable, which was -1.995469, then Ho was rejected. N-Gain earned amounted to 0.569775. As a result, there was a difference in the value of Natural Science style material after using Student Worksheets or LKS android-based. Keywords:  Student Worksheets, Natural Science Subject, Worksheets Andorid Based